2015
DOI: 10.3923/ajar.2015.132.138
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Leaf Chlorophyll Concentration, Photosynthetic Activity and NK Concentration of Elaies guineensis Via Correlated SPAD-502 Chlorophyll Index

Abstract: Determination of chlorophyll contents often requires destructives analysis and involves lengthy procedures while measurement on photosynthetic rate requires specialized equipment that often limits extensive in-field application. SPAD chlorophyll meter gives indirect measurement of leaf chlorophyll contents in a rapid, non-destructive and convenient manner. The use of SPAD meter for each individual plant species require calibration curve for each individual plant species, as the accuracy of the estimation are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The non-destructive measurements of chlorophyll content (SPAD Index) [30] measured by El-nakhel et al [31], reflected the changes obtained regarding chlorophyll pigment measurements in our work. Indeed, chlorophyll increased significantly with lettuce maturation, and in both harvest stages was significantly higher in red Salanova, which was the exact same trend observed with chlorophyll measurements of lettuce at 4 and 19 DAT [31].…”
Section: Pigments and Total Ascorbic Acid Content Of Microgreens And supporting
confidence: 80%
See 1 more Smart Citation
“…The non-destructive measurements of chlorophyll content (SPAD Index) [30] measured by El-nakhel et al [31], reflected the changes obtained regarding chlorophyll pigment measurements in our work. Indeed, chlorophyll increased significantly with lettuce maturation, and in both harvest stages was significantly higher in red Salanova, which was the exact same trend observed with chlorophyll measurements of lettuce at 4 and 19 DAT [31].…”
Section: Pigments and Total Ascorbic Acid Content Of Microgreens And supporting
confidence: 80%
“…Indeed, chlorophyll increased significantly with lettuce maturation, and in both harvest stages was significantly higher in red Salanova, which was the exact same trend observed with chlorophyll measurements of lettuce at 4 and 19 DAT [31]. In photosynthetic tissues, carotenoids, and chlorophylls a and b operate in light harvesting and perform tasks in photo-protection by quenching free radicals, singlet oxygen, and other reactive species [30]. In our case, this is expected with lettuce growth, accompanied by an increase in the plants leaf area, implicating a higher light interception by the plants and consequently a higher need of light harvesting and photo-protection.…”
Section: Pigments and Total Ascorbic Acid Content Of Microgreens And supporting
confidence: 79%
“…The increase in chlorophyll content indicated that the photosynthetic rate was increased and led to plant health, growth promotion, and fruit production, as shown by the growth parameters measured in this study ( Table 3). Chlorophyll content (SPAD-502) was highly correlated with photosynthetic rate as well as the leaf nitrogen and potassium concentrations (Sim et al, 2015). Nitrogen plays a pivotal role in the inorganic nutrition of plants, determining growth (Mengel, 1994;Marschner, 1997) and as a major component of chlorophyll (Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The plants total chlorophyll content influences its photosynthesis rate [46], which correlated to the productivity [47]. The chlorophyll content results from the measurements then compared with the leaf greenness as observed by the drone camera.…”
Section: Methodsmentioning
confidence: 99%